Asian Paleocene charophyte records demonstrate Eocene dispersals from Asia to Europe - Cao, Wenxin; Li, Sha; Li, Qiang; Stidham, Thomas A.; Wan, Xiaoqiao; Ni, Xijun (Journal of paleontology, 2022)
A latest Paleocene charophyte flora collected from the South Gobi area in the Junggar Basin, western China, includes the geographically widespread taxa Peckichara torulosa var. varians (Dollfus and Fritel, 1919) Sanjuan, Vicente, and Eaton, 2020, Lychnothmanus vectensis (Groves, 1926) Soulié-Märsche, 1989, and Gyrogona lemani capitataGrambast and Grambast-Fessard, 1981. Lychnothmanus vectensis (as Lychnothmanus aff. L. vectensis) is known from the Cretaceous–Paleocene transition in eastern China and the latest Paleocene in western China, with likely additional records from the United States (Utah). The earliest European records of L. vectensis are from the late Eocene to early Oligocene in Spain, France, and England. Similarly, the oldest record of G. lemani capitata is from the latest Paleocene in the South Gobi area, with younger records from the middle Eocene of France. These latest Paleocene gyrogonite assemblages demonstrate the origin of these charophyte lineages in Asia. The dispersal of these charophytes from Asia to Europe in the middle to late Eocene appears to have occurred before the retreat of the Turgai Strait in both the Tarim area and the Siberian Basin by the end of the late Eocene and before the “Grande Coupure” in Europe and the Mongolian Remodelling in Asia during the Eocene–Oligocene transition. We hypothesize that waterbirds may have facilitated this intercontinental dispersal, and that idea is supported by the shared occurrence of avian groups in Central Asia and Europe in the middle and late Eocene.